Effectiveness of participatory ergonomics intervention on musculoskeletal health and psychosocial factors among selected manufacturing industry workers in Selangor, Malaysia - Lim, Chee Siang (2017)
Introduction: Musculoskeletal diseases (MSDs) are the most reported occupational diseases worldwide, as well as in Malaysia. Participatory ergonomics (PE) intervention was recommended as one of the promising strategy to prevent musculoskeletal problems at the workplace. However, the evidence for its effectivenes s was lacking and was not found in the manufacturing industry of Malaysia.Objective: The primary aim of this study was to determine the effectiveness of PE intervention to improve musculoskeletal health and psychosocial factors among manufacturing industry workers. Methodol og y: A to tal o f 436 wo rkers wh o fu lfilled t h e in clu s iv e an d exclu s iv e crit eri a were selected from 9 manufacturing companies in Selangor using multistage sampling method. The study design of this study was Solomon-four group, in which the participants were randomly assigned into 4 groups by departmental levels: pretested intervention or control group, or non-pretested intervention or control group. The PE intervention program could be divided into 3 phases. Phase 1 was the walkthrough survey at workplace and development of PE intervention module, phase 2 was PE training and implementation of changes, and phase 3 was follow up. The intervention group was given PE intervention while the control group was given hearing conservation program. The main outcomes measured included musculoskeletal symptoms (MSS) and levels of musculoskeletal pain at 9 body regions (Nordic Questionnaire), perceived stress (PSS-10), chronic s tres s (CSSS), depres s ion and anxiety (DASS-21), and ps ychos ocial work factors (JCQ). Data were collected by using validated questionnaire before intervention (pretest) and 3 months after intervention (posttest). Results: This study suggested high prevalence of overall MSS (78.3%) and multi-site pain (MSP) (48.3%), with lower back (57.9%) being the most complained anatomica l sites. Several characteristics such as female, obese, current and former smokers, having sleep problems occasionally and longer work duration were associated with higher prevalence of MSS. The psychosocial factors remained healthy, with majority of respondents reported low level of mental stress, emotional states and psychosocial work factors. Higher level of chronic stress, depression and anxiety were reported among workers with following characteristics: males, work position as supervisors, migrant , long work duration and low work salary. After adjusting for sociodemographic, health and work characteristics, psychosocial factors and MSS were reciprocally associated, where chronic stress, depression, anxiety and job strain significantly predicted MSS and, vice versa, MSS at neck, upper back and MSP significantly predicted chronic stress, depression, anxiety and job strain. In addition, Structural Equation Modelling (SEM ) concluded the roles of mental stress and emotional states (β= 0.17) as the mediators for the relationship between psychosocial work factors and MSS. The effectiveness of PE intervention was evaluated using sequential analyses for Solomon four-group design.The PE intervention had accounted for about 11% to 28% of reduction to the prevalence of MSS at single anatomical region and 30% of reduction to that of MSP among pretested workers. A two-way MANOVA revealed significant main effect of intervention on the reduction of total musculoskeletal pain collectively. Levels of musculoskeletal pain at almost all the anatomical sites had reduced significantly in the intervention group, except for elbow, hand and thigh regions. The findings also revealed that PE intervention was more effective than the control group in improving psychosocial factors by lowering the levels of chronic stress, depression, anxiety and psychological job demand. Conclus ion: This study showed that PE intervention could effectively improv e musculoskeletal health and psychosocial factors among manufacturing industry workers.Psychosocial factors and musculoskeletal health were reciprocally associated, with mental stress and emotional states mediated the relationship between psychosocial work factors and MSS.